2019
DOI: 10.1111/nmo.13602
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in a crude extract of Catha edulis inhibit rat intestinal contraction via blocking Ca2+ channels

Abstract: Background Animal studies show that Catha edulis inhibits gastrointestinal tract motility. However, there is little or no information on its effect on colon motility and the mechanism of action and active constituents responsible for this effect. This study therefore attempted to discern the effect, suggest the mechanism, and identify the active compounds from the crude extract. Methods A crude extract of Catha edulis was fractionated and subfractionated using column chromatography and HPLC. The activity of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…TtM contains many phenolic and flavonoid compounds, including quercetin, kaempferol, tiliroside, astragalin, and isoquercitrin [49]. It has been reported that quercetin reduces peristalsis [45], whereas kaempferol impairs intestinal transit in mice through α-2 adrenergic receptors and calcium channels [50]. However, flavonoids appear also to be involved in NO production and in the inhibition of calcium and potassium channels, leading to endothelium smooth muscle relaxation [51].…”
Section: Discussionmentioning
confidence: 99%
“…TtM contains many phenolic and flavonoid compounds, including quercetin, kaempferol, tiliroside, astragalin, and isoquercitrin [49]. It has been reported that quercetin reduces peristalsis [45], whereas kaempferol impairs intestinal transit in mice through α-2 adrenergic receptors and calcium channels [50]. However, flavonoids appear also to be involved in NO production and in the inhibition of calcium and potassium channels, leading to endothelium smooth muscle relaxation [51].…”
Section: Discussionmentioning
confidence: 99%
“…The compound P-2-1 was identified as quercetin, of which the characters were previously reported [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the relationship between key compounds and GMD. It is known that quercetin, which has the most target genes, blocks Ca2+ channels and inhibits intestinal contraction [ 18 ]. In addition, resveratrol was reported to have a function of inducing the relaxation of gastric smooth muscle through high-conductivity calcium-activated potassium channels [ 19 ].…”
Section: Discussionmentioning
confidence: 99%